Por uma ressignificação semiótica da telenovela como instrumento educativo na prática de ensino - Magalhães, Eva de (2021)
Soap operas are not the most praised media – inside or outside scholar and academic studies. They are, however, accessible to students through broadcast television, and they also may shape students’ opinions. But one can think of this scenario as an opportunity for educational reconstruction. During classes, with the help of the teacher in charge, students might be able to identify and to reframe concepts presented by soap operas and even look at them through a different perspective. Based on The Taming of the Shrew (1594), a play by William Shakespeare, which inspired the Brazilian soap opera O Cravo e a Rosa (2000), this paper aims to be an educational intervention proposal, using soap operas as a multiple semiotic learning source. Considering a hybrid approach as a possible way of learning fundamental semiotic signs, and also Literature themes, the main objective of this research is to use technology as a school ally, and television media as a bridge to students’ daily lives. The first question to be made is: can soap operas be a semiotic tool to teacher’s work in teaching/learning process? Our hypothesis is that the verbal language of the script and the non-verbal language of soap opera’s audiovisual presentation are both sources of exercises to a more significant educational development to teachers and students when based on a semiotic dialogue closer to Literature. The general objective is to analyze the praxis of teaching/learning in classes, and to develop an interventional proposal of an inter-semiotic dialogue between soap operas and Literature in Middle School, especially in eighth grade. The qualitative methodology was applied based on our own teaching experience, considering soap operas inspired by literary works as a possible contribution to creative projects during classes, and also trying to relate them with other technological media. The main theoretic references we use are: Arlindo Machado (2003; 2010) Paulo Freire (1996; 2013), Deleuze (1997); Lucia Santaella (2004; 2016); Márcia Fusaro (2018); Ana Maria Haddad Baptista (2012); and Décio Pignatari (2003).